Efficacy of meglumine antimoniate treatment on boxer Leishmania infantum skin lesions: case report - Carresi, Cristina; Ferrucci, Clara Francesca; Mangano, Cyndi; Coppoletta, Anna Rita; Cardamone, Antonio; Musolino, Vincenzo; Gliozzi, Micaela; Mollace, Vincenzo; Britti, Domenico (Frontiers in Veterinary Science, 2025)
This clinical report describes the beneficial effects of local subcutaneous injections of meglumine antimoniate (Glucantime®) on Leishmania cutaneous lesions in a dog from Calabria, a region of Southern Italy. Leishmaniasis is an endemic zoonotic disease in the European Union, particularly in Mediterranean countries, as well as in parts of north and east Africa, India, China, and Central and South America, caused by protozoa of the genus Leishmania spp., which infect several reservoirs, including humans and domestic animals. In southern Europe, the main etiological agent is Leishmania infantum, transmitted by sandflies of the subfamily Phlebotominae, which is the most common cause of cutaneous leishmaniasis (CL) in these regions, where dogs are considered the primary domestic reservoir of the parasite. A 7-year-old male non-sterilized Boxer named Ettore underwent pre-vaccination blood tests and Leishmania indirect immunofluorescence (IFI) test, which confirmed the presence of antibodies against the protozoan Leishmania infantum (antibody titer, 1:1280), supporting the diagnosis of CL. The dog underwent a therapeutic protocol consisting of miltefosine (Milteforan™ - Virbac®) (2 mg/Kg b.w. per os) for 28 days and allopurinol 300 mg (10 mg/Kg b.w. po) for 6 months. However, at the end of the treatment period, the appearance of a suspicious skin lesion on the left tarsus was reported, which appeared inflamed and infected. The subsequent antibiotic and anti-inflammatory therapy based on amoxicillin+clavulanic acid (12.5 mg/kg b.w. po for 15 days), metronidazole (75000UI + 12.5 mg po for 15 days), and prednisone (0.5 mg/kg b.w. po for 10 days) failed to be effective; thus, the lesion worsened and also spread to the dorsal femoral surface of both hind limbs, presenting as blackish, swollen, painful, alopecic and oozing bloody and purulent material. Mild renal microlithiasis and splenopathy were reported by abdominal ultrasound and were associated with a possible leishmania pattern. Finally, skin lesions were experimentally treated with subcutaneous injections of Glucantime® (200 mg/lesion – 0.5 mL/lesion) once a month for 5 months, followed by complete healing. Interestingly, the experimental localized treatment with Glucantime® proved to be crucial in counteracting Leishmania skin lesions. The results obtained suggest that, through an appropriate diagnosis, it is possible to define targeted and effective therapeutic protocols useful in the management of canine leishmaniasis.